Pengaruh Model Pembelajaran Blended Learning dan Kreativitas Siswa Terhadap Hasil Belajar IPA Siswa Kelas VII - Andri Irwansyah Irwansyah; Lukman Nulhakim; Suherman Suherman (BIOEDUSCIENCE, 2023)
Background: This study aims to analyze differences in student learning outcomes between students whose learning uses a learning model (blended learning) and has high student creativity and students whose learning uses a learning model (discovery learning) and has high student creativity. Method: This study uses a quantitative method approach. This type of research uses a 2x2 factorial experiment method. The research population used was all students of class VII SMPN Labuan. Result: The results showed that: 1) There were differences in science learning outcomes between students whose learning activities used the blended learning model and students who used the discovery learning model. 2) There are differences in science learning outcomes between students who have high creativity and students who have low creativity. 3) There are differences in science learning outcomes between students who use blended learning models and have high creativity and students who use discovery learning models and high creativity. Conclusion: There are differences in science learning outcomes between students who use the blended learning model and have low creativity and students who use the discovery learning model and have low creativity.